Mobbing at the Workplace and its Relation to Employees’ Quality of Working Life and Overall Life: A Qualitative Study in Greece - Meramveliotakis, Ilias; Kalaitzaki, Argyroula (Journal of Psychology and Psychotherapy Research, 2019)
Mobbing is a type of psychological violence, in which an individual becomes the target of disrespectful or harmful behavior at the workplace. The aim of the present study was to examine the mobbing behaviors and its effect on employees’ quality of working life, physical and mental health. Potential measures and interventions implemented by both the employees and employers were also investigated. Qualitative data was collected using a semi-structured interview, in a convenience sample of 10 employees working in the private sector of management services, in Heraklion, Crete, Greece, who had been victims of mobbing. The semi-structured interview included questions about demographics, the mobbing behavior, the outcomes of mobbing at the individual and organizational level (i.e., mental and physical health, job satisfaction and productivity) and any potential measures undertaken. The results showed that employees had been mobbed by their superiors (80%) or colleagues (20%). The most frequently reported mobbing behaviors were employees being gossiped about, criticized for their capabilities, laughed at by others and ignored. High levels of mobbing reportedly affected employees’ mental health negatively as expressed by high levels of anxiety, sadness, irritability, aggression, fear, lack of pleasure, feelings of injustice, loneliness, withdrawal and memory problems. Employees’ physical health also decreased as was evident by health problems, eating disorders, vomiting, muscle aches, headaches, migraines, dizziness, stomach pains, hypertension, sleeping disorders and tachycardia. Mobbing also influenced employee’s workplace behavior, as they reported a gradual decrease in job satisfaction and job performance at a rate of at least 30-40%. The results of this study will guide policymakers to develop prevention and intervention programs focusing on reducing mobbing behaviors and improving employees’ quality of working life and overall quality of life.